OBEDIENTES À LEI E TEMENTES A DEUS: Ação dos Indígenas na Capitania do Maranhão Diante das Denúncias do Auditório Eclesiástico e Advento das Reformas Pombalinas (1755-1765) - LOUREIRO, Maria Rosalina Bulcão (2022)
The present dissertation analyzes the indigenous protagonism, especially of women, in the Capitania of Maranhão in the second half of the 18th century, in the time frame from 1755 to 1765, based on the complaints of espousal, incest, alcouce, marriage impediments and prostitution initiated in the Ecclesiastical Court. The functioning of an Ecclesiastical Court, directly involved with social discipline and reform of customs, came about with the creation of the bishopric of Maranhão in 1677. The existence of a diocese in colonial Amazonia since the end of the 17th century, in a region whose known Catholicism was that introduced by the missionaries, already demonstrates that the presence and performance of the secular clergy, subordinate to the bishop and responsible for parish life and administration of sacraments, cannot be disregarded over the indigenous populations. Using documentation from the Ecclesiastical Court and other sources, we sought to connect, in a pioneering and unprecedented way, the indigenous history and the history of the Church in Maranhão from issues such as indigenist legislation, labor force exploitation, Pombal reform and repression of customs. Starting from the source of the Ecclesiastical Tribunal, seventeen denunciations were examined in this dissertation with the objective of bringing another perspective of the interaction between natives and the Church from the bishopric of Maranhão and the actions of the secular clergy. The time frame of the dissertation also aimed to analyze the Pombaline Directory as a project of civilization, work and marriage to the indigenous populations, evaluating the action and imbrication of the spiritual and secular arm in relation to the natives in the Captaincy of Maranhão. In addition, we sought to recover the meanings and trajectories of the indigenous and mestizo women denounced in the Ecclesiastical Court. The vast documentation presented showed that, more than a series of radical reforms, the measures implemented by Pombal had as a characteristic the continuity of measures previously put in place. In addition, it was verified that in Portugal, the importance of the dioceses and the concern with the disciplining of customs increased after the Tridentine Council, moving to the colonial territory the creation of bishoprics vigilant to the Tridentine precepts. This fact had repercussions in the vigilance and repression of the natives, especially in the issue of Christian marriage, since the majority of the denunciations of courtship. The documentation also allows us to construct a narrative that evidences the performance of indigenous women in the Capitania of Maranhão, acting as general and specialized labor force, obtaining advantages in stable concubinages, sustaining themselves in the activity of prostitution and many other experiences that allow the deconstruction of strongly rooted stereotypes.